'Shari'ah corporation': the legal entity of corporation from the Malaysian law and shari'ah perspective - Abd Ghadas, Zuhairah Ariff; Abdul Rahman, Nasarudin; Hassan, Halyani (Inderscience Enterprises Ltd., 2013)
Under the Malaysian law which is based on the English law, companies are recognised as a legal person and the metaphor of corporate personality is used to justify the company’s legal framework. As a creature of the statute, companies’ totally depend on the Companies Act. On the other hand, under Shari’ah, the existence of business entity is based upon agreement between the parties and the legal basis of Shari’ah business structure is the contractual principles. With the recent rapid development in Shari’ah compliance businesses in Malaysia, such as Islamic finance and halal products, there is a question on whether Shari’ah businesses could be carried out in a civil law business structure. This paper analyse companies’ legal framework under the Malaysian law and compare them with the principles of Shari’ah. The outcome of this paper is a proposal for a legal framework of an Islamic corporation.